2021
DOI: 10.1093/nar/gkab179
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for substrate recognition and cleavage by the dimerization-dependent CRISPR–Cas12f nuclease

Abstract: Cas12f, also known as Cas14, is an exceptionally small type V-F CRISPR–Cas nuclease that is roughly half the size of comparable nucleases of this type. To reveal the mechanisms underlying substrate recognition and cleavage, we determined the cryo-EM structures of the Cas12f-sgRNA-target DNA and Cas12f-sgRNA complexes at 3.1 and 3.9 Å, respectively. An asymmetric Cas12f dimer is bound to one sgRNA for recognition and cleavage of dsDNA substrate with a T-rich PAM sequence. Despite its dimerization, Cas12f adopts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 38 publications
2
72
0
Order By: Relevance
“…Interestingly, the single mutations at D143, T147, and E151 showing improved activity are near or in a (D/E)XRKN motif that is highly conserved in the Cas12a family (Figure 1J), suggesting that this domain could be important in regulating Cas12f-DNA interaction. Confirming this hypothesis, we aligned these mutations to very recently reported Cas12f structures and observed that they reside in the DNA binding pocket (Figures S4B and S4C;Takeda et al, 2021;Xiao et al, 2021). The variant D326A/D510A/D143R/T147R/K330R/E528R was chosen for further characterization for endogenous gene activation, which we refer to simply as ''dCasMINI'' hereafter.…”
Section: Technologymentioning
confidence: 59%
“…Interestingly, the single mutations at D143, T147, and E151 showing improved activity are near or in a (D/E)XRKN motif that is highly conserved in the Cas12a family (Figure 1J), suggesting that this domain could be important in regulating Cas12f-DNA interaction. Confirming this hypothesis, we aligned these mutations to very recently reported Cas12f structures and observed that they reside in the DNA binding pocket (Figures S4B and S4C;Takeda et al, 2021;Xiao et al, 2021). The variant D326A/D510A/D143R/T147R/K330R/E528R was chosen for further characterization for endogenous gene activation, which we refer to simply as ''dCasMINI'' hereafter.…”
Section: Technologymentioning
confidence: 59%
“…RNP complex stoichiometry. The cryo-electron microscopic (cryo-EM) structure of Un1Cas12f1 9,13 revealed that one gRNA and two Un1Cas12f1 nucleases comprise the RNP effector complex. Here, using mass photometry 14 , we evaluated the oligomeric state of SpCas12f1 and AsCas12f1 nucleases in the apo-form, in a binary complex with its gRNA and bound to a dsDNA target in a ternary complex (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although sharing low sequence similarity, REC1 13–102 is structurally similar to the REC1 C domain in Cas12f (Figs. 2D and S3B,C) , which forms the dimerization interface in Cas12f (Takeda et al, 2020; Xiao et al, 2021). However, the key hydrophobic residues (I118, Y121, Y122, I126) in Cas12f are not conserved in REC1 13–102 (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…2A,B,E and S3B) . The Nuc domains or equivalent domains are inevitably present in all Cas12 proteins with structures determined to date including Cas12a (Dong et al, 2016; Gao et al, 2016; Nishimasu et al, 2017; Stella et al, 2017; Stella et al, 2018b; Swarts and Jinek, 2019; Swarts et al, 2017; Yamano et al, 2016; Yamano et al, 2017; Zhang et al, 2019), Cas12b (Liu et al, 2017; Wu et al, 2017; Yang et al, 2016), Cas12e (Liu et al, 2019), Cas12f (Takeda et al, 2020; Xiao et al, 2021), Cas12g (Li et al, 2021) and Cas12i (Huang et al, 2020; Zhang et al, 2020), and play an essential role in the nuclease activity. Second, the lid motif of Cas12k is longer than that of Cas12f and is in a closed conformation that covers the pseudonuclease site (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation